Localized scleroderma and related comorbidities: a single centre cohort study - Kortelainen, Saara; Hieta, Niina; Rissanen, Tiia; Paltta, Johanna; Pirilä, Laura; Kähäri, Veli-Matti (Oxford University Press (OUP), 2026)
Background: Localized scleroderma, or morphea is a rare autoimmune disease that affects the skin and underlying tissue. It is more common in females than males. The incidence has two peaks, one in childhood and another in middle-age. Concomitant autoimmune diseases are frequently observed, whereas systemic sclerosis occurs rarely simultaneously.
Objectives: This study aimed to assess the clinical features, comorbidities, and treatments of localized scleroderma in Southwest Finland.
Methods: Patients diagnosed with localized scleroderma (ICD-10 code L94) treated between January 1, 2005 and November 30, 2020, were identified from the hospital discharge register of Turku University Hospital. Diagnoses were classified into five main types and their subtypes based on the European Dermatology Forum (EDF) criteria. Basic demographic data, associated comorbidities, treatments used, and their efficacy were collected.
Results: A total of 155 patients with morphea were included, with 125 females (80.6%) and 30 males (19.4%). The most common subtype was limited, plaque-type morphea (n=71, 45.8% of all patients), followed by the generalized type (n=57, 36.8%). Fifty-nine concomitant autoimmune diseases were identified in 45 patients (29.0%), most frequently autoimmune thyroid diseases (n=23, 14.8%). Simultaneous systemic sclerosis was rare (n=3, 1.9%). The most common malignancy was breast cancer (n=11, 7.1%). Extracutaneous manifestations were more common in pediatric-onset patients (18.5%) than in adult-onset patients (1.7%). The most commonly used systemic treatment was methotrexate (n=25, 16.1%) which was beneficial for 64% of treated patients. Phototherapy was administered to 63 patients (40.6%) and it was beneficial for 49 patients (77.8%).
Conclusions: Patients with morphea at our centre often required systemic immunomodulatory treatment or phototherapy. The incidence of the generalized subtype and the occurrence of concomitant autoimmune diseases, particularly thyroid autoimmune diseases, were relatively high. No evidence of an increased risk of malignancy was observed among these patients.